Differentially expressed tRNA-derived fragments in bovine fetuses with assisted reproduction induced congenital overgrowth syndrome - Goldkamp, Anna K.; Li, Yahan; Rivera, Rocio M.; Hagen, Darren E. (Frontiers in Genetics, 2022)
As livestock producers wish to rapidly improve genetic merit in their herd, assisted reproductive technologies (ART) have become increasingly popular. Utilizing ART can cause an increased risk of the congenital overgrowth syndrome, Large Offspring Syndrome (LOS), in ruminants. Dysregulation of transcripts has been observed in bovine fetuses with LOS, suggesting a cause of the phenotype. Our recent study identified variations in tRNA expression in LOS individuals, leading us to hypothesize that variations in tRNA expression can influence the availability of their processed regulatory products, tRNA-derived fragments (tRFs). Due to their resemblance in size to microRNAs, studies suggest that tRFs target mRNA transcripts and regulate gene expression. Thus, we have sequenced small RNA isolated from skeletal muscle and liver of bovine fetuses to elucidate mechanisms contributing to LOS. Moreover, we utilized our previous tRNA sequencing data to analyze the contribution of tRNA availability to tRF abundance. 22,289 and 7,737 unique tRFs were predicted in the liver and muscle tissue respectively. The greatest number of reads originated from 5’ tRFs in muscle and 5’ halves in liver. In addition, mitochondrial (MT) and nuclear derived tRF expression was tissue-specific with most MT-tRFs and nuclear tRFs derived from LysUUU and iMetCAU in muscle, and AsnGUU and GlyGCC in liver. Despite variation in tRF abundance within treatment groups, we identified differentially expressed (DE) tRFs across Control-AI, ART-Normal, and ART-LOS groups with the most DE tRFs between ART-Normal and ART-LOS groups. Many DE tRFs target transcripts enriched in pathways related to growth and development in the muscle and tumor development in the liver. Finally, we found positive correlation coefficients between tRNA availability and tRF expression in muscle (R=0.47) and liver (0.6). Our results highlight the dysregulation of tRF expression and its regulatory roles in LOS. These tRFs were found to target both imprinted and non-imprinted genes in muscle and genes linked to tumor development in liver. Furthermore, we found that tRNA transcription is a highly modulated event that plays a part in the biogenesis of tRFs. This study is the first to investigate the relationship between tRNA and tRF expression in combination with ART-induced LOS.